12. Clinical and neurophysiological predictors of vasculitic neuropathy diagnosed on nerve biopsy. Issue 4 (April 2018) - Nathani, Dev; Barnett, Michael; Pollard, John D.; Spies, Judith; Wang, Min-Xia; Kiernan, Matthew C.
Abstract : Purpose: The diagnosis of vasculitic neuropathy (VN) relies on a typical neurological presentation, combined with clinical neurophysiology and pathological confirmation. Nerve biopsy has suboptimal sensitivity, is costly and risks procedural complications. Hence, the present study was undertaken to identify the clinical and neurophysiological factors most predictive of a histopathological diagnosis of vasculitis. Methods: The clinical, neurophysiological and histopathological features of 208 patients presenting for nerve biopsy over 21 months were analysed. Biopsy results were categorised into 'Definite', 'Probable', 'Possible' and 'Absent' VN based on guidelines from the Peripheral Nerve Society (2010). T-test and χ 2 (or Fisher's exact) test was used to compare clinical factors between the cohorts. Results: From the total cohort of 208 patients, 66 patients were clinically suspected to harbour a diagnosis of vasculitis, 10.6% of whom were diagnosed with 'Definite VN'. Only 2 patients not suspected of VN were diagnosed with 'Definite VN'. 20% of patients with 'Definite or Probable VN' had non-systemic VN. Female gender was more common in 'Definite or Probable VN' (26.6% vs 14.5%; OR 1.5; p = 0.036). A predominant axonal neuropathy evident on nerve conduction studies (NCS) predicted 'Definite or Probable VN' (85.2% vs 64.5%; OR 1.3; p = 0.04). P-ANCA positivity predicted 'Definite VN' (75% vs 1.4%; p < 0.001), while 80% of patients with elevated rheumatoid factor (RF) had 'Definite or Probable VN'. Pain was more prevalent in the 'Definite VN' group. 'Probable VN' patients were significantly younger compared to other patient cohorts. In terms of referral bias, non-neurologist referral more commonly predicted 'Definite VN' (44.4% vs 10.8% from Neurologists; OR 4.1; p = 0.003). Conclusions: ANCA positivity and primary axonal neuropathy on NCS were the predictors most suggestive of an underlying diagnosis of VN, with the presence of pain and RF positivity trending towards a positive association. The predictive power of a non-neurologist referral may be explained by high proportion of referrals originating from specialties associated with vasculitic complications, particularly rheumatology, haematology and immunology.